First evidence for multimodal animal seed dispersal in orchids - Karremans Lok, Adam Philip (2022)
Identifying the mechanisms for seed dispersal and persistence of species is a central aim of ecology. Seed dispersal by animals is an essential form of dissemination in many plant communities, including seeds of over 66% of neotropical canopy tree species.1,2 Besides physical dispersal, animals influence seed germination probabilities through scarification, breaking dormancy, and preventing rotting, so plants often invest important resources in attracting them. Orchids are predominantly adapted to wind dispersal, having dust-like seeds that are easily uplifted. Exceptions include bird-,3,4 cricket-,5,6 and mammal-dispersed7 species, featuring fleshy fruits with hard seeds that germinate after passing the animal’s digestive system. Given the similarity in fruit and seed morphology, zoochory has also been suggested in Vanilla,8–15 a pantropical genus of 118 species with vine-like growth.16–18 We test this prediction through in situ and ex situ experimentation using fruits of Va- nilla planifolia, and wild relatives, from which vanillin—a widely used natural aroma and flavoring—is obtained. Seeds from dehiscent fruits are removed by male Euglossini collecting fragrances, a unique case in plants, and female Meliponini bees gathering nest-building materials, a first among monocots. By contrast, mammals, mostly rodents, consume the nutritious indehiscent fruits, passing the seeds up to 18 h after consumption. Protocorm formation in digested and undigested seeds proves that scarification in the gut is not strictly required for germination. Multimodal seed dispersal mechanisms are proven for the first time in Orchidaceae, with ectozoochory and endozoochory playing crucial roles in the unusually broad distribution of Vanilla.